Syntaxin 1B regulates synaptic GABA release and extracellular GABA concentration, and is associated with temperature‐dependent seizures. Issue 5 (27th September 2020) - Mishima, Tatsuya; Fujiwara, Tomonori; Kofuji, Takefumi; Saito, Ayako; Terao, Yasuo; Akagawa, Kimio
Abstract: De novo heterozygous mutations in the STX1B gene, encoding syntaxin 1B, cause a familial, fever‐associated epilepsy syndrome. Syntaxin 1B is an essential component of the pre‐synaptic neurotransmitter release machinery as a soluble N ‐ethylmaleimide‐sensitive factor attachment protein receptor protein that regulates the exocytosis of synaptic vesicles. It is also involved in regulating the functions of the SLC6 family of neurotransmitter transporters that reuptake neurotransmitters, including inhibitory neurotransmitters, such as γ‐aminobutyric acid (GABA) and glycine. The purpose of the present study was to elucidate the molecular mechanisms underlying the development of febrile seizures by examining the effects of syntaxin 1B haploinsufficiency on inhibitory synaptic transmission during hyperthermia in a mouse model. Stx1b gene heterozygous knockout ( Stx1b +/− ) mice showed increased susceptibility to febrile seizures and drug‐induced seizures. In cultured hippocampal neurons, we examined the temperature‐dependent properties of neurotransmitter release and reuptake by GABA transporter‐1 (GAT‐1) at GABAergic neurons using whole‐cell patch‐clamp recordings. The rate of spontaneous quantal GABA release was reduced in Stx1b +/− mice. The hyperthermic temperature increased the tonic GABAA current in wild‐type (WT) synapses, but not in Stx1b +/− synapses. In WT neurons, recurrent bursting activities were reduced in a GABA‐dependent manner at hyperthermic temperature; however, this was abolished in Stx1b +/− neurons. The blockade of GAT‐1 increased the tonic GABAA current and suppressed recurrent bursting activities in Stx1b +/− neurons at the hyperthermic temperature. These data suggest that functional abnormalities associated with GABA release and reuptake in the pre‐synaptic terminals of GABAergic neurons may increase the excitability of the neural circuit with hyperthermia. Abstract : Syntaxin 1B regulates the exocytosis of synaptic vesicles and reuptake of GABA by GABA transporters (GAT). Here we examined the molecular mechanisms underlying the development of febrile seizures by the effect of syntaxin 1B haploinsufficiency on inhibitory synaptic transmission during hyperthermia. The rate of spontaneous quantal GABA release was reduced in Stx1b +/− mice. The hyperthermic temperature increased the tonic GABAA current in wild‐type synapses, but not in Stx1b +/− synapses. These findings suggest functional abnormalities associated with GABA release and reuptake in the pre‐synaptic terminals of GABAergic neurons increase the excitability of the neural circuit with hyperthermia.